Framework Administered Account for Selected Fund Activities : Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) Subaccount. (Policy Papers; Policy Paper, 2009)
In March 2009, the Fund established a new Framework Administered Account to administer external financial resources for selected Fund activities (the 'SFA Instrument'). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of a subaccount within the SFA. The subaccount for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) Topical Trust Fund ('TTF') would be the second one under the SFA. This paper requests Executive Board approval to establish the AML/CFT TTF subaccount (the 'Subaccount') under the terms of the SFA Instrument.